Elevated N‐terminal prohormone of brain natriuretic peptide among persons living with HIV in a South African peri‐urban township. (25th June 2020) - Peterson, Tess E.; Baker, Jason V.; Wong, Lye‐Yeng; Rupert, Adam; Ntusi, Ntobeko A. B.; Esmail, Hanif; Wilkinson, Robert; Sereti, Irini; Meintjes, Graeme; Ntsekhe, Mpiko; Thienemann, Friedrich
Abstract: Aims: Efforts to improve access to antiretroviral therapy (ART) have shifted morbidity and mortality among persons living with HIV (PLWH) from AIDS to non‐communicable diseases, such as cardiovascular disease (CVD). However, contemporary data on CVD among PLWH in sub‐Saharan Africa in the current ART era are lacking. The aim of this study was to assess the burden of cardiac stress among PLWH in South Africa via measurement of N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP). Methods and results: NT‐proBNP was measured at baseline in 224 PLWH enrolled in a sub‐study of a tuberculosis vaccine trial in Khayelitsha township near Cape Town, South Africa. Thresholds were applied at the assay's limit of detection (≥137 pg/mL) and a level indicative of symptomatic heart failure in the acute setting (>300 pg/mL). Mean ( SD ) age of participants was 39 (6) years, 86% were female, and 19% were hypertensive. Mean ( SD ) duration of HIV diagnosis was 8.3 (3.9) years and CD4 + count was 673 (267) with 79% prescribed ART for a duration of 5.6 (2.7) years. Thirty‐one percent of participants had NT‐proBNP > 300 pg/mL. Elevated vs. undetectable NT‐proBNP level was associated with older age ( P  = 0.04), no ART ( P  = 0.03), and higher plasma tumour necrosis factor‐α ( P  = 0.01). Conclusions: Among South African PLWH largely free of known CVD and on ART with high CD4 + counts and few comorbidities, we observed a high proportion with elevated NT‐proBNP levels, suggesting the burden of cardiac stress in this population may be high. This observation underscores the need for more in‐depth research, including the current effect of HIV on heart failure risk among a growing ART‐treated population in sub‐Saharan Africa.